Is air pollution a risk factor for rheumatoid arthritis? - Essouma, Mickael (J Inflamm (Lond), 2015)
Rheumatoid arthritis is a chronic inflammatory debilitating disease triggered by a complex interaction involving genetic and environmental factors. Active smoking and occupational exposures such as silica increase its risk, suggesting that initial inflammation and generation of rheumatoid arthritis-related autoantibodies in the lungs may precede the clinical disease. This hypothesis paved the way to epidemiological studies investigating air pollution as a potential determinant of rheumatoid arthritis. Studies designed for epidemiology of rheumatoid arthritis found a link between traffic, a surrogate of air pollution, and this disease. Furthermore, a small case–control study recently found an association between wood smoke exposure and anticyclic citrullinated protein/peptide antibody in sera of patients presenting wood-smoke-related chronic obstructive pulmonary disease. However, reports addressing impact of specific pollutants on rheumatoid arthritis incidence and severity across populations are somewhat conflicting. In addition to the link reported between other systemic autoimmune rheumatic diseases and particulate matters/gaseous pollutants, experimental observation of exacerbated rheumatoid arthritis incidence and severity in mice models of collagen-induced arthritis after diesel exhaust particles exposure as well as hypovitaminosis D-related autoimmunity can help understand the role of air pollution in rheumatoid arthritis. All these considerations highlight the necessity to extend high quality epidemiological researches investigating different sources of atmospheric pollution across populations and particularly in low-and-middle countries, in order to further explore the biological plausibility of air pollution’s effect in the pathogenesis of rheumatoid arthritis. This should be attempted to better inform policies aiming to reduce the burden of rheumatoid arthritis.